The Associations between Loss and Posttraumatic Stress and Depressive Symptoms Following Hurricane Ike. Issue 4 (12th July 2013) - Paul, Lisa A.; Price, Matthew; Gros, Daniel F.; Gros, Kirstin Stauffacher; McCauley, Jenna L.; Resnick, Heidi S.; Acierno, Ron; Ruggiero, Kenneth J.
<x xml:space="preserve">Abstract</x> Disasters can have wide‐ranging effects on individuals and their communities. Loss of specific resources (e.g., household contents, job) following a disaster has not been well studied, despite the implications for preparedness efforts and postdisaster interventions. Objective To provide information about the effects of loss on postdisaster distress, the present study assessed associations between disaster‐related variables, including the loss of specific resources, and postdisaster distress. Method Random‐digit dialing methodology was used to recruit hurricane‐affected adults from Galveston and Chambers, TX, counties one year after Hurricane Ike. Data from 1, 249 survivors were analyzed to identify predictors of distress. Results Variables that were significantly associated with posttraumatic stress disorder symptoms included sustained losses, hurricane exposure, and sociodemographic characteristics; similar results were obtained for depressive symptoms. Conclusions Together, these findings suggest risk factors that may be associated with the development of posthurricane distress that can inform preparedness efforts and posthurricane interventions.